Well, if this were an equation = 0 and I was asked to solve for x or find the x-intercepts, the first thing I would do is multiply everything by the least common denominator of 12 to get:
12x^2 - 11x +2 which will then factor as (3x - 2)(4x - 1).
Does this help you any?
2007-04-03 05:22:45
·
answer #1
·
answered by birdwoman1 4
·
2⤊
0⤋
Would it help if you multiply the equation by 12? To get
12x^2 - 11 + 2 That factors to
(4x - 1)(3x - 2) don't forget to multiply by 1/12 to get the original value back again.
2007-04-03 12:20:29
·
answer #2
·
answered by rscanner 6
·
2⤊
0⤋
When all else fails, use the quadratic formula.
x = {- (-11/12)+/- sqrt([11/12]2 - 4/6)}/2
2 x = 11/12 +/-sqrt( 121/144 - 2/3)
2 x = 11/12 +/-sqrt( [121-96]/144)
2x = 11/12 +/- 5/12
x = 11/24 +/- 5/24 x= 2/3, 1/4
then (x-2/3)(x-1/4) is the factoring.
2007-04-03 12:26:14
·
answer #3
·
answered by cattbarf 7
·
2⤊
0⤋
Multiply this by 12:
12x^2-11x+2
(4x-1)(3x-2)
2007-04-03 12:32:53
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
Multiply by 12
12x^2-11x+2
(4x-1)(3x-2)
x=1/4;-2/3
2007-04-03 12:36:48
·
answer #5
·
answered by Dave aka Spider Monkey 7
·
1⤊
0⤋
x^2-11/12x+1/6
take the LCM of all the terms:
x^2/1-11/12x+1/6=0
12(x^2)-1(11x) +2(1)
----------------------- =0
12
12x^2-11x+2
------------------ =0
12
12x^2-11x+2 =0
factors 0f (12 x 2=24, which will give eleven when added up is -8,-3)
12x^2-8x-3x+2=0
3x(4x-1) -2(4x-1)
(4x-1) (3x-2)
4x-1=0, 3x-2=0
4x=1, 3x=2
x=1/4, x=2/3
2007-04-03 12:32:11
·
answer #6
·
answered by omo 2
·
2⤊
0⤋
x^2-11/12x+1/6
=(12x^3-11+2x)/12x
2007-04-03 13:25:18
·
answer #7
·
answered by Bubblez 3
·
1⤊
0⤋